“DIFFERENT THOUGH THE SEXES ARE, THEY INTERMIX”: GENDER SHIFTS IN VIRGINIA WOOLF’S ORLANDO: A BIOGRAPHY - Kappke, Nathalie de Souza; Maggio, Sandra Sirangelo (Revista do GEL, 2020)
The following article discusses how gender shifts are portrayed in the novel Orlando: A Biography (1928), by Virginia Woolf. Since the beginning of the novel, Orlando is presented as a very talented, unique creature, with a great aptitude for writing. Also, Orlando is depicted as an adaptable person, who shifts his behavior according to what is expected from him in different situations. Besides, Orlando goes through sex change in the middle of the story. Accepting the fantastic happenings of the narrative as real, this work investigates which impact this transformation has in Orlando’s life. Examining the sex change and also the gender shifts the protagonist undergoes through ideas presented by Judith Butler in Gender Trouble (1990) and by Sandra Bem in the essays “Sex Typing and Androgyny: Further Explorations of the Expressive Domain” and “Sex Role Adaptability: The Consequence of Psychological Androgyny”, this research has identified that Orlando does not restrain theirself to only one gender, but waves through different genders. Thus, adapting themself to what is required in each situation.